A paleoecological context for forest distribution and restoration in Grootbos Nature Reserve, Agulhas Plain, South Africa - Prader, Sabine; Gillson, Lindsey; Strauss, Paula; Privett, Sean D. J.; Hoffman, M. Timm (Frontiers in Conservation Science, 2024)
Grootbos Nature Reserve falls within the Cape Floristic Region of South Africa and comprises fynbos and forest vegetation elements, which exist as alternate stable states and are naturally maintained by feedbacks between vegetation, fire, topography and climate. The objective of this study was to investigate changes in forest extent in the Baviaansfontein valley in Grootbos Nature Reserve in order to understand whether current forest coverage was greater or lesser prior to colonial settlement. Incorporating paleoecology has the potential to define historical ranges of landscape variability that can guide forest restoration programs that are aligned to historical forest occurrence. Not all landscapes are suited for tree planting initiatives as they harbor indigenous open vegetation, which is of conservation value. Historical and palaeoecological information is especially valuable as tree planting initiatives and reforestation programs are becoming more popular. Here we present a combined palynological (pollen, spores, charcoal) and geochemical approach (X-ray fluorescence elemental ratios, Loss-on-ignition), to evaluate the historic extent and distribution of forest and fynbos vegetation for the past ~250 years at Baviaansfontein in the Grootbos Nature Reserve. The start of the record was dominated by pollen typical of asteraceous fynbos, with evidence of forest elements also present, though in low abundance. After 200 years (c.1750 CE–1950 CE) of increased input of micro- and macrocharcoal, the subsequent decline in charcoal indicates a decrease in fire occurrence. This decline coincides with increased input of forest pollen taxa, suggesting that fire suppression most likely triggered forest expansion and perhaps initiated the beginning of a biome boundary shift. The continued decline in fire promoted the development of the present-day proteoid fynbos type around ~1980 CE and was responsible for the replacement of the previously more asteraceous-dominated fynbos type. The results show that changes in fire occurrence have driven compositional changes over time within fynbos but also contributed to the expansion of forest at the expense of fynbos. Considering the palaeoecological record and the expected warmer climate with more fires, forest expansion at Baviaansfontein is not recommended. The proteoid-dominated fynbos biome might be similarly negatively affected by warmer climate and a shift to an asteraceous fynbos community could occur in the future.